Point-of-Care Ultrasound in the Sequential Diagnosis of Postoperative Cardiac, Pulmonary, and Vascular Complications Following Thoracoabdominal Aortic Aneurysm Repair: A Case Report and Pathophysiological Review - Agil Tri Hutomo; Septian Adi Permana (HM Publisher, 2025)
Background: Open repair of a thoracoabdominal aortic aneurysm (TAAA) is a formidable surgical undertaking associated with profound physiological stress and a high risk of life-threatening postoperative complications. We present a case where a sequential, multi-system point-of-care ultrasound (POCUS) protocol was instrumental in unraveling a cascade of distinct but interconnected postoperative complications. Case presentation: A 67-year-old male with a Crawford Type II TAA underwent an elective open repair. His postoperative course in the Intensive Care Unit (ICU) was complicated by a cascade of events. On postoperative day one, he developed hypotensive shock. Bedside cardiac ultrasound revealed new-onset, severe left ventricular systolic dysfunction (ejection fraction 20-25%), indicative of profound myocardial stunning. By day three, this was followed by progressive hypoxemic respiratory failure. Lung ultrasound identified a large, compressive left-sided pleural effusion, which was contributing to his respiratory decline. On day four, the patient developed signs of acute left lower limb ischemia. Vascular ultrasound confirmed a complete occlusive thrombus in the popliteal artery. This rapid series of diagnoses, all made at the bedside with POCUS, facilitated targeted interventions including the initiation of inotropic support, goal-directed diuretic therapy, and emergency surgical thrombectomy, leading to a successful patient outcome. Conclusion: This case highlights the unique diagnostic power of a structured, serial POCUS examination in the complex post-TAAA patient. It demonstrates how this non-invasive modality can effectively diagnose a